Komunitas Parasitoid Lalat Pengorok Daun pada Pertanaman Sayuran Dataran Tinggi - Rustam, Rusli; Rauf, Aunu; Maryana, Nina; Pudjianto, Pudjianto; Dadang, Dadang (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2008)
Leafminer fly, Liriomyza spp. are widely known as new important pests attacking many vegetable species inhigh land in Indonesia. The objective of the research was to study community of parasitoid leafminer in highaltitude, and parasitization level. This research also looked at more specific on parasitization level caused byOpius chromatomyiae. There were four species of leafminer recorded from the survey, Liriomyza huidobrensis,Liriomyza sativae, Liriomyza chinensis and Chromatomyia horticola. The observation also found eight species ofparasitioid associated with collected leafminers. Six species of recorded parasitoid belonged to family of Eulopidae,and two rest species belonged to Braconidae and Eucoilidae respectively. Those eight species of parasitoids wereHemiptarsenus varicornis, Asecodes deluchii, Neochrysocharis okazakii, Neochrysocharis formosa ,Neocrhysocharis sp. Quadrastichus liriomyzae, Opius chromatomyaie, Gronotoma micromorpha. ParasitoidOpius chromatomyiae and Hemiptarsenus varicornis were found to be dominant in the range altitude between1001-1300 and 1301-1600 asl. From 16 spesies of hosts attacked by leaf miners, only Opius chromatomyiae wasrecorded to have ability to parasitize the leafminer in 13 host species with parasitization level reached 1,84–62,26%.